"A Tale of Two Croatias": How Club Football (Soccer) Teams Produce Radical Regional Divides in Croatia's National Identity. Issue 1 (24th January 2021) - Tsai, Dustin Y.
Abstract: Croatia's monumental second-place finish at the 2018 FIFA World Cup represents the highest football achievement to date for the young nation. This victory, however, masks violent internal divisions between its domestic club football teams. This article examines the most salient rivalry between Dinamo Zagreb and Hajduk Split, two teams that have evolved to represent the interests of Croatia's north and south, respectively. Using interviews with radical football fans, I argue that the two teams act as reservoirs for regional identity-building while violence between their fans is a microcosm for political and economic tensions between Zagreb and Split. More importantly, this rivalry exposes the dividedness of the Croatian state, as it continues to grapple with the complexity of its radical regional identities in the wake of its independence from Yugoslavia. This article contributes to the existing body of literature on sports identity and regionalisms/nationalism as well as how sporting teams shape the geographies of belonging.